Enhancing English Learning in Arab Israeli Teacher Education - Jamal Assadi; Tareq Murad (Eximia, 2024)
This research explores the profound importance of incorporating the mother tongue in English Teacher Education programs, aiming to uncover potential benefits and challenges. The study provides insights for educators, curriculum developers, and policymakers by scrutinizing motivation, cultural relevance, and language acquisition impact. Embracing the mother tongue holds the potential to create a more effective and engaging learning environment for English language learners. The research involves an in-depth analysis of how the mother tongue acts as a bridge for complex linguistic concepts, making the learning experience more accessible. Simultaneously, challenges are acknowledged, considering potential misconceptions and the need for effective pedagogical strategies. In essence, this study contributes substantively to the discourse on language education, providing evidence-based insights into the mother tongue in English teacher education programs. The expected outcomes guide the refinement of language learning strategies, empowering educators, curriculum developers, and policymakers to optimize teacher education programs for linguistic proficiency and cultural resonance among English language learners, utilizing a qualitative case study approach.